The Occurrence of Arabic to Javanese Phonological Interference in Bahtsul Masail Discussions at Darul Huda Islamic Boarding School, Ponorogo - Nur Aini Syah; Bagas Muhyidin Abid; Edy Purnomo (Universitas Sebelas Maret, 2025)
Interference can be considered a form of error in language. The emergence of interference can damage the linguistic rules of a language, potentially leading to confusion and disorder, as it deviates from established norms or grammatical structures. One of the most common forms of interference is phonological interference, particularly in bilingual contexts such as Islamic boarding schools (pesantren). This study aims to describe the forms of phonological interference from Arabic into Javanese that occur during Bahtsul Masail activities at the Darul Huda Islamic Boarding School in Mayak, Ponorogo. Additionally, this research seeks to identify the consonant patterns that contribute to the interference and the underlying causal factors. This study uses descriptive qualitative method with data collection techniques including interviews, audio recordings, and field notes. The researcher directly participated in the Bahtsul Masail sessions, engaged in dialogues with participants, and recorded instances of phonological interference that emerged during students' arguments. The findings reveal that: (1) the forms of phonological interference include sound substitution, simplification of pronunciation, and accent adaptation in the articulation of Arabic by Javanese speakers; and (2) Phonological interference is influenced by several factors, including the learning environment in pesantren, students’ everyday language use, and Arabic teaching approaches that inadequately cover phonological elements.